2009
DOI: 10.17221/913-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Hydrogen Peroxide Formation on Apoptosis Induction by Olive Oil Phenolic Compounds

Abstract: Abstract:In the present investigation the ability of different phenolic compounds, either present or not in olive oil, to induce both apoptosis on tumour cells and H 2 O 2 accumulation in cell culture medium was assesed. Among the phenols studied we found that tyrosol (p-HPEA), homovanillic alcohol and protocatechuic, o-coumaric, vanillic, homovanillic, ferulic and syringic acids did not induce either apoptosis on HL60 cells or H 2 O 2 accumulation, while hydroxytyrosol (3,4-DHPEA), 3,4-dihydroxyphenylacetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…The lack of cytotoxicity in HL-60 experiments that we have found for SY is in accordance with previous determination that indicated no cytotoxic effect of SY in extracts of Elaphomyces granulates at concentrations up to ~31 µg·mL −1 using this cell line [ 65 ]. Moreover, Fabiani et al [ 66 ] found that SY did not induce apoptosis in HL-60 cell when is applied to the cell medium at a concentration of 0.1 mM. It has been reported that SI biotransformation by plant peroxidases results in an anticarcinogenic effect from its derivates in HL-60 cells [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lack of cytotoxicity in HL-60 experiments that we have found for SY is in accordance with previous determination that indicated no cytotoxic effect of SY in extracts of Elaphomyces granulates at concentrations up to ~31 µg·mL −1 using this cell line [ 65 ]. Moreover, Fabiani et al [ 66 ] found that SY did not induce apoptosis in HL-60 cell when is applied to the cell medium at a concentration of 0.1 mM. It has been reported that SI biotransformation by plant peroxidases results in an anticarcinogenic effect from its derivates in HL-60 cells [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…A partir dos dados obtidos, os autores sugeriram que a porção catecol dos fenóis é necessária, mas não suficiente para induzir a apoptose e a acumulação de H2O2. Além disso, o metabolismo do hidroxitirosol pode reduzir parcialmente seu potencial pró-apoptótico e a atividade pró-apoptótica da forma dialdeídica do ácido elenólico ligada ao hidroxitirosol e ao tirosol não é mediada pela atividade de liberação de H2O2 (Fabiani et al, 2009b). Somado a isso, os compostos fenólicos possuem potentes capacidades antioxidantes e anti-inflamatórias, além dos efeitos anticarcinogênicos utilizando a linhagem celular HL60, tratadas com diferentes componentes do azeite para avaliar as propriedades antitumorigênica dos fenóis na proliferação, apoptose e diferenciação.…”
Section: Outros Tipos De Câncerunclassified